Linear recursive networks and their applications in topological design and data routing. - Jing, Hsu Wen (Computer communication review.)
We present a new class of interconnection topologies called the Linear Recursive Networks. It is shown that each member of this fairly large class of network topologies possesses a recursively-decomposable structure. The path and connectivity properties of the entire class of networks are analyzed and found to have useful features. It is also demonstrated that Point-To-Point or Broadcasting/Gathering operations can be performed efficiently on all Linear Recursive Networks. The preliminary results suggest that the Linear Recursive Networks potentially have many applications.